Application of Tax Treaties to Investment Funds - Pallesi, Niccolò (Editorial Pontificia Universidad Javeriana y Facultad de Ciencias Jurídicas, 2007)
Among financial investors, investment funds are the ones that mostly have increased their importance in capital markets where the regulation on investment funds is still incipient. By using investment funds, individual investors can have the possibility to participate in various companies as well as in market places worldwide without the need of specific and elaborated knowledge of the same companies and markets. After an introductory chapter I start analyzing the definition and activity of an investment fund, attention is also paid to the UCITS regulation for European investment funds. In the next chapter I analyze how investment funds are taxed in specific EU Member Countries (i.e. Italy and Luxembourg), in theUnited States and also how investment funds are treated in offshorejurisdictions.The core chapter of the paper discusses the possible application of tax treaties to investment funds, in particular from the perspective of the state of source. The definition of beneficial owner and the treatment of income distributed from an investment fund are also analyzed in depth. The same chapter also focuses on the possible application of the OECD Partnership Report to investment funds.Based on my findings the last chapter is dedicated to some final considerations about the application of tax treaties to investment funds. I have always been fascinated by capital markets, their techniques and the tax treatment of income arising from investments in capital markets. I think that this paper represents a great possibility of acquiring special knowledge in a topic that I always liked. Moreover, another reason that encouraged me to choose this topic is the fact that still not many scholars have written about such a hot topic, convincing me to contribute to the discussion thereof. My objective is to analyze the possible application of tax treaties to investment funds in order to provide some suggestions as a valid starting point for a future deeper analysis.